Neurocognitive outcomes in adolescents with and without four weeks of cannabis abstinence: a randomized clinical trial using contingency management - Schuster, Randi M.; Costello, Meghan A.; Potter, Kevin; Torquati, Matteo; Gilman, Jodi M.; Evins, A. Eden (Frontiers in Psychiatry, 2025)
BackgroundAs adolescent cannabis use becomes more common, questions remain about the potential for neurocognitive recovery after stopping cannabis use.MethodThis study examined whether short-term abstinence from cannabis leads to cognitive improvements. A total of 238 adolescents (ages 13–19; 51% female; 55% White, 18% Black, 9% Asian, 18% other races) from Greater Boston participated, including 154 adolescents who regularly used cannabis (CB) and 84 adolescents with no cannabis use (NU). Participants who used cannabis were randomized to incentivized abstinence (CB-Abst) or a non-contingent monitoring control (CB-Mon). Non-users completed four weeks of monitoring (NU). Participants completed tests of executive function, memory, and attention weekly for four weeks.ResultsAt baseline, CB adolescents demonstrated worse verbal memory and processing speed than NU on (p <.006). CB-Abst performance was similar to that of the NU group at week 4. At week 4, those in the CB-Abst group showed greater improvements in inhibitory control compared to the CB-Mon group (β = -10.9, p = .037). There were no significant differences between CB groups in memory or attention task performance at week 4. Exploratory analyses revealed modest gains across all groups in some tasks.DiscussionBrief cannabis abstinence may be associated with improvements in executive function among adolescents, supporting the idea of neurocognitive recovery, which has important implications for treatment, prevention, and public health policies.